BAHASA PADA PAPAN PETUNJUK OBJEK WISATA DI YOGYAKARTA BERDASARKAN RANAH TEMPAT (LANGUAGE ON SIGNBOARD OF TOURISM OBJECT IN YOGYAKARTA BASED ON DOMAIN) - Wening Handri Purnami (Balai Bahasa Sulawesi Utara, 2018)
The object of this study is the use of language on the signboards of tourism object based on the domain. The problem studied is how the type and form of language on the signboard. The purpose of this study is to describe the type and form of language on the signboard. The theory used in the study is structurally prescriptive. This study uses qualitative descriptive methods and observation techniques. The results of the study show that the type of language used in the signboards of the tourism object was Indonesian, Javanese, and English. The embodiment of the language used is in the form of words, phrases, and sentences. Based on the domain, the signboards inform the name of the tourism object, attraction places, and public facilities of the tourism objects.